Parental Attitudes and Hesitancy About COVID-19 vs. Routine Childhood Vaccinations: A National Survey - Temsah, Mohamad-Hani; Alhuzaimi, Abdullah N.; Aljamaan, Fadi; Bahkali, Feras; Al-Eyadhy, Ayman; Alrabiaah, Abdulkarim; Alhaboob, Ali; Bashiri, Fahad A.; Alshaer, Ahmad; Temsah, Omar; Bassrawi, Rolan; Alshahrani, Fatimah; et al. (Frontiers in Public Health, 2021)
Objectives: To quantify parental acceptance of the COVID-19 vaccine and assess the vaccine hesitancy (VH) for COVID-19 versus childhood vaccines. Methods: Eight vaccine hesitancy scale (VHS) items, adopted from WHO’s Strategic Advisory Group of Immunization (SAGE), were used to assess VH for COVID-19 vaccine vs routine childhood vaccines. We distributed the online survey to parents with the commence of the national childhood COVID-19 vaccination program in Saudi Arabia. Results: Among 3167 parents, 47.6% are decided to vaccinate their children against COVID-19. The most common reasons for refusal were inadequate safety information (69%) and worry about side effects (60.6%). Parents have a significantly greater positive attitudes toward children's routine vaccines versus the COVID-19 vaccine, with higher mean VHS (±SD) =2.98 ±0.58 versus 2.63±0.73, respectively (p-value<0.001). Parents agreed more that routine childhood vaccines are more essential and effective as compared to the COVID-19 vaccine (Cohen’s D: 0.946, and 0.826, consecutively; T-test p-value <0.00). There is more parental anxiety about serious side effects of the COVID-19 vaccine versus routine childhood vaccines (Cohen’s D = 0.706, p-value< 0.001). Parents who relied on the Ministry of Health information were more predicted (OR=1.28, p-value=0.035) to intend to vaccinate as opposed to those who used the WHO website (OR=0.47, -53%, p-value<0.001). In a multivariate logistic regression analysis, the factors associated with intention to vaccinate children were parents who received COVID-19 vaccine, older parents, having children aged 12-18, and parents with lower education levels. Conclusions: Significant proportion of parents are hesitant about the COVID-19 vaccine because they are less confident in its effectiveness, safety, and whether it is essential for their children. Relying on the national official healthcare authority’s website for the source of information was associated with increased acceptance of childhood COVID-19 vaccination. As parental intention to vaccinate children against COVID-19 is suboptimal, healthcare authorities could boost vaccine uptake by campaigns targeting hesitant parents.